Heuristic Reflection for Teachers for Better Learning Teaching Interaction - WIjayanti, Rosalia Hening (Indonesian Journal of English Language Studies (IJELS), 2015)
A reflection on teaching is a way to maintain and improve teachers‘ competence which is officially required. One of the reflection sessions to conduct is the end-meeting reflection.The reflection helps teachers evaluate their teaching practice which has been done to confirmthe accomplishment of lesson objectives and to improve their future teaching quality.However, the absence of reflection activity occurs not due to the lack of awareness about theimportance of reflection, but mainly because of the administrative work load and the tightteaching schedule. Therefore, the researcher aims to propose a reflection model to conformteachers‘ insufficient time in doing a reflection. The theories of reflection and the feedbackfrom practitioners underlie the proposed heuristic five-minute end-meeting reflection modelwhich can be done at the junior high school level. Keywords: reflection, heuristic, professional competence, pedagogic competence